Sosialisasi Dampak Upah Minimum terhadap Kesejahteraan Pekerja Informal di Kab. Karawang - Abas, Muhamad; Hidayat, Anwar; Guntara, Deny; Targana, Tatang (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The government has established a comprehensive labor protection system as a result of the decline in workers' income levels. The aim of this effort is to ensure that workers' fundamental rights are fulfilled and that adequate welfare is provided for workers and their families, while taking into account the evolution of the investment and business industries. To understand the impact of the minimum wage on the welfare of informal workers in Karawang Regency, this study uses a mixed-method approach that combines quantitative and qualitative methods. According to path analysis, there is a path coefficient of 0.31 (p 0.05), which indicates that there is an indirect influence from other variables, such as macroeconomic stability, the effectiveness of social protection programs, and the demographic characteristics of informal workers. However, the results of the study on the adaptation strategies of informal workers and the effectiveness of social protection programs in Karawang Regency show a structural gap between labor policy designs that focus on the formal sector and the real conditions of informal workers, especially those with fluctuating incomes and high mobility.